2019
DOI: 10.1159/000500231
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Predictors of Adverse Acute Kidney Injury Outcomes in Critically Ill Patients: The Dublin Acute Biomarker Group Evaluation Study

Abstract: Background: The Dublin Acute Biomarker Group Evaluation (DAMAGE) Study is a prospective 2-center observational study investigating the utility of urinary biomarker combinations for the diagnostic and prognostic assessment of acute kidney injury (AKI) in a heterogeneous adult intensive care unit (ICU) population. The objective of this study is to evaluate whether serial urinary biomarker measurements, in combination with a simple clinical model, could improve biomarker performance in the diagnostic prediction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…There have been few predictive models using urine biomarkers for prediction of AKI and AKI outcomes. Mcmahon et al demonstrated the addition of urinary NGAL/albumin to the clinical model modestly improved the prediction of AKI, in particular severe stage 3 AKI and the prediction of 30-day RRT or death 24 . The TRIBE study showed that postoperative urine IL-18 and plasma NGAL improved AKI prediction over clinical model alone from AUC of 0.69 to 0.76 and 0.75, respectively 21 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been few predictive models using urine biomarkers for prediction of AKI and AKI outcomes. Mcmahon et al demonstrated the addition of urinary NGAL/albumin to the clinical model modestly improved the prediction of AKI, in particular severe stage 3 AKI and the prediction of 30-day RRT or death 24 . The TRIBE study showed that postoperative urine IL-18 and plasma NGAL improved AKI prediction over clinical model alone from AUC of 0.69 to 0.76 and 0.75, respectively 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was highlighted in the 2012 KDIGO AKI guidelines, which first proposed a decrement in serum creatinine of $50% occurring within a week as a retrospective definition of AKI (1). Similarly, in our recent prospective study of a critically ill cohort, we used a threshold of a $33% decrease from the intensive care unit admission (reference) serum creatinine during the first 7 days to identify patients with recovering AKI at admission (10). An additional 177 AKI cases (26% of total cohort, added to 38% who developed AKI by standard KDIGO criteria; with an overall AKI incidence of 65%) were identified using this criterion.…”
Section: Epidemiologic Data and Observational Studies Of Aki Recoverymentioning
confidence: 99%
“…The mechanism by which urinary L-FABP affects prognosis is yet to be elucidated but may be related to L-FABP being a marker that reflects systemic organ ischemia. Urinary L-FABP is considered a useful marker for renal ischemia [3][4][5], and in cases where urinary L-FABP is high, ischemia may occur in other organs. Thuijls et al reported a link between increased urinary L-FABP levels and intestinal damage [8].…”
Section: Discussionmentioning
confidence: 99%
“…We found that urinary L-FABP-positive cases were significantly associated with AKI development when compared to L-FABP-negative cases; however, there was no such association observed with mortality. In contrast, urinary L-FABP was reported to predict AKI as a renal ischemia marker from an early stage [ 3 , 4 ]. Contrary to our previous findings, Doi et al reported an association between urinary L-FABP and 14-day mortality, in addition to the onset of AKI [ 5 ].…”
Section: Introductionmentioning
confidence: 99%